A Comprehensive, Flexible Collection of SARS-CoV-2 Coding Regions. Issue 9 (1st September 2020) - Kim, Dae-Kyum; Knapp, Jennifer J; Kuang, Da; Chawla, Aditya; Cassonnet, Patricia; Lee, Hunsang; Sheykhkarimli, Dayag; Samavarchi-Tehrani, Payman; Abdouni, Hala; Rayhan, Ashyad; Li, Roujia; Pogoutse, Oxana; et al.
Abstract: The world is facing a global pandemic of COVID-19 caused by the SARS-CoV-2 coronavirus. Here we describe a collection of codon-optimized coding sequences for SARS-CoV-2 cloned into Gateway-compatible entry vectors, which enable rapid transfer into a variety of expression and tagging vectors. The collection is freely available. We hope that widespread availability of this SARS-CoV-2 resource will enable many subsequent molecular studies to better understand the viral life cycle and how to block it.